Direct and indirect damage zone of radiofrequency ablation in porcine lumbar vertebra - Zhang, Chao; Feng, Jinyan; Liu, Yongheng; Zhang, Yan; Song, Weijie; Ma, Yulin; Han, Xiuxin; Wang, Guowen (Frontiers in Oncology, 2023)
Objectives To explore the direct and indirect heat damage zone of radiofrequency ablation (RFA) in porcine vertebrae and to verify the safety of RFA in vascularized vertebral tumor model. Methods RFA was performed in the porcine lumbar vertebrae. Magnetic resonance (MR) imaging, hematoxylin and eosin (HE), and terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL) were used to assess the extent of direct and indirect injuries after RFA. The cavity of lumbar vertebrae was made, and the adjacent muscle flap was used to fill the cavity to make vertebrae tumor model. RFA was performed in vascularized vertebral tumor model. Results T1-weighted images showed hypointensive region in the center surrounded by a more hypointensive rim on day 0 and 14. T2-weighted images showed that RFA zone was a hypointensive region on day 0. It was the hypointensive region in the center surrounded by a hyperintensive rim on day 7. HE showed that the RFA zone could be clearly observed on day 14. Thin bone marrow loss areas were seen around the RFA zone, which was consistent with hyperintensive rim on T2-weighted images. TUNEL showed a large number of apoptotic cells in the RFA zone. During RFA in the vertebral tumor model, the temperature of all monitoring positions was less than 45 ℃. Conclusion In vivo experiments, the effective zone of RFA was evaluated by MR imaging and pathology, and the direct and indirect damage range were obtained. The safety of RFA was verified by RFA in vascularized vertebral tumor model.